PENGARUH MANAJEMEN SARANA DAN PRASARANA PEMBELAJARAN TERHADAP MUTU HASIL PEMBELAJARAN MATA PELAJARAN PRODUKTIF PADA JURUSAN ADMINISTRASI PERKANTORAN DI SMK KOTA CIMAHI - Edora, - (2011)
The study focused on the quality of about the low quality of learning evaluation in produvtive subjects Office Administration majors are characterized by the end of school exam results are below the minimum criteria for graduation.This research was aimed to capture the portrail of learning facilities and infrastructure management, the picture quality of learning outcomes and the influence of learning infrastructure and facilities management towards the quality of learning outcomes productive subjects majoring in Office Administration. The study consisted of two variables, they are Infrastructure Management Learning and Quality Learning Outcomes variables.This research employed survey methods, the data were obtained by observation, library research, questionnaires, and interviews. The research involved of 36 teachers at SMK Programs Office administrative CITY OF CIMAHI. Questionnaire used is a Likert scale models. The data were analized by using the Pearson correlation coefficient and simple regression analysis.The result showed that was influence between Learning Management facilities and Infrastructure. Based on these data can be concluded that the learning management infrastructure consisting of indicators of planning, procurement, storage, inventory, maintenance, and removal has been going well, but not optimal. It could be proove by the result of the quationares shows that there are some respondents in the conduct of the management of facilities and infrastructure are still learning sometimes. After measuring by the scale continuum from six indicators of learning facilities and infrastructure management, it can be concluded that the deletion indicator is a low level category. The thing that they have to do are monitoring and improving the infrastructure and facilities management activities conducted by school parties, especially the removal of facilities and infrastructure indicators of learning.